Existence and Uniqueness of Solutions for Singular Higher Order Continuous and Discrete Boundary Value Problems. (15th January 2008) - Yuan, Chengjun; Jiang, Daqing; Zhang, You
Abstract : By mixed monotone method, the existence and uniqueness are established for singular higher-order continuous and discrete boundary value problems. The theorems obtained are very general and complement previous known results.